The linkages between risk perception, attitude and behavioural intention : investigation on financial investment among individuals prior to prime saving vears - Lim, Thien Sang (2017)
Decision making among individuals with regard to financial investment is a complicated process. Relying on modern financial theory is inadequate to explain behaviours of individual investors because it focuses solely on the objective risk as the determinant for making investment decision. In personal finance industry, having a long-term and meaningful client-advisor relationship is vital. One way to achieve this is when there is a good understanding of risk perception, attitude and risk-taking behaviour on both sides. Clearly, research results from risk perception in the behavioural finance theory would further strengthen and consolidate the understanding on how individuals make financial decision. This research aims to identify the predictors of risk perception and determine the central role of risk perception in affecting risk taking behaviours. The research framework was based on Perception Formation Model (PFM) with further support from the Theory of Planned Behaviour, decision making models under risk, and knowledge-attitude-behaviour model. Data were collected from Peninsula Malaysia, Sarawak and Sabah involving 492 individual income earners below the age of prime savings years. Nineteen hypotheses were tested using AMOS Structural Equation Modelling software and SPSS Macro PROCESS Model 6. Four predictors: subjective knowledge, peer influence, internet influence, and risk propensity were significantly and positively associated with favourable risk perception. Consistent with the PFM, favourable risk perception showed a direct association with the intention to invest. Although, objective knowledge did not demonstrate a significant direct association with behavioural intention, there were significant indirect effects between objective knowledge and intention to invest via three specific indirect paths where risk perception and attitude stood as simple and sequential mediators. Subjective knowledge showed a stronger effect than objective knowledge as the former demonstrated significant effect on behavioural intention directly and indirectly. The supportive results for mediation tests allowed the conclusion that risk perception and attitude played a significant central role to explain risk taking behaviour in financial investment. How the findings implicate the theory, methodology, and industry were also discussed. Finally, some suggestions to expand research in the field of behavioural finance, particularly in risk perception were also included.